Will Rogers : cowboy philosopher - Malone, Mary. (Springfield, N.J. : Enslow Publishers, 1996)
Follows the private and public life of the humorist and social critic, from his childhood in Oklahoma through his years as a cowboy to his rise to fame as an entertainer.
Includes bibliographical references (p. 126) and index.
Keywords: Rogers, Will, -- 1879-1935 -- Juvenile literature; Rogers, Will, -- 1879-1935.; Entertainers -- United States -- Biography -- Juvenile literature; Humorists, American -- 20th century -- Biography -- Juvenile literature; Entertainers; Humorists; Cherokee Indians -- Biography; Indians of North America -- Biography